2011
DOI: 10.2528/pierb11051302
|View full text |Cite
|
Sign up to set email alerts
|

Investigation on Propagation Characteristics of Super-Gaussian Beam in Highly Nonlocal Medium

Abstract: Abstract-We investigate the propagation characteristics of superGaussian beam in highly nonlocal nonlinear media. The optical beam propagation has been modeled by well known nonlocal nonlinear Schrödinger equation. The variational method is employed to find the initial beam propagation parameters and then split step Fourier method is used for numerical simulations. A generalized exact analytical solution of the model is obtained and critical power of soliton is determined. The evolution of super-Gaussian beam … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…Traditionally, phase retrieval algorithms, such as phase unwrapping max-flow algorithm (PUMA), can fail to give accurate results when phase (and depth) gradients are large. 30 To investigate the performance of TIE + LC and TIE + TPE with LC for the reconstruction of phases (and topographies) with sharper edges, we consider a super-Gaussian, which has larger spectral content and tends to a top-hat function for higher values of the order n. The super-Gaussian phase considered here is defined as 31,32 E Q -T A R G E T ; t e m p : i n t r a l i n k -; e 0 2 0 ; 1 1 7 ; 2 0 4…”
Section: Object With Uniform Intensity and Super-gaussian Phasementioning
confidence: 99%
See 1 more Smart Citation
“…Traditionally, phase retrieval algorithms, such as phase unwrapping max-flow algorithm (PUMA), can fail to give accurate results when phase (and depth) gradients are large. 30 To investigate the performance of TIE + LC and TIE + TPE with LC for the reconstruction of phases (and topographies) with sharper edges, we consider a super-Gaussian, which has larger spectral content and tends to a top-hat function for higher values of the order n. The super-Gaussian phase considered here is defined as 31,32 E Q -T A R G E T ; t e m p : i n t r a l i n k -; e 0 2 0 ; 1 1 7 ; 2 0 4…”
Section: Object With Uniform Intensity and Super-gaussian Phasementioning
confidence: 99%
“…To investigate the performance of TIE + LC and TIE + TPE with LC for the reconstruction of phases (and topographies) with sharper edges, we consider a super-Gaussian, which has larger spectral content and tends to a top-hat function for higher values of the order n. The super-Gaussian phase considered here is defined as 31 , 32 φ=φmax exp{(x2+y2w02)n}; n=2.…”
Section: Simulations Of Unwrapped Phase Retrieval Using Tie + Lc and ...mentioning
confidence: 99%
“…Note that the nonlocal nonlinearity which can support a variety of nonlocal spatial optical solitons exhibits in many physical systems, and some of them have been observed experimentally [3][4][5][6][7][8][9][10]. Moreover, it has been reported that a great number of optical beams can steadily propagate in SNNM under sufficient conditions, including Gaussian beams and higher-order Gaussian beams, four-petal Gaussian beams, Lorentz-Gaussian beams, the beams carrying wave front dislocations such as Hermite-, Hermite-cosh-or Laguerre-Gaussian beams, and so on [11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26]. As well known, pure wave front dislocations in a monochromatic wave are divided into two types: one is the longitudinal screw dislocation which is also known as the optical vortex with spiral phase, and the other is the transverse edge dislocation with π-phase shift located along a line in the transverse plane.…”
Section: Introductionmentioning
confidence: 99%
“…Also, a class of stable self-similar waves has been reported with a conservative nonintegrable system with quintic nonlinearity engineered by doping a Kerr medium with resonant impurities [31]. Different types of beam profiles have been adopted to excite AS in highly nonlocal media, to name a few, Gaussian profile [1,6], super-Gaussian profile [32], the Hermite-Gaussian (HG) profile [33], Laguerre-Gaussian profile [8], cosh-Gaussian profile [34], Ince-Gaussian profile [35,36], complex-variable-function Gaussian profile [37], and variable sinh-Gaussian profile [38]. Hermite-Gaussian spatiotemporal soliton is found in a (3+1)-dimensional partially nonlocal nonlinear system [39].…”
Section: Introductionmentioning
confidence: 99%